HEGEMONI IDIOLOGIS TOTAL DALAM FILM ALIF LAM MIM KARYA ANGGY UMBARA - Doni Purnawan; Sri Yanuarsih; I Wayan Letreng (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study examines the representation of ideological hegemony in the film Alif Lam Mim by Anggy Umbara, which reflects the socio-political dynamics of Indonesia in the future. As a mass communication medium, film not only functions as entertainment but also serves as a means of education and social criticism. This film depicts the dominance of military and religious institutions in restricting individual freedoms through a hegemonic system of power. This research uses a descriptive qualitative approach with Antonio Gramsci’s theory of hegemony as the analytical framework. Gramsci classifies hegemony into three forms: total hegemony, declining hegemony, and minimal hegemony. Total hegemony is seen through state domination that is voluntarily accepted by society without significant resistance. This is reflected in news broadcasts that normalize violence and obscure its structural roots. Declining hegemony emerges when characters in the film begin to question the system and show inner resistance, although not yet openly. Meanwhile, minimal hegemony is marked by explicit resistance to power, rejection of media manipulation, and the emergence of conflict between personal awareness and dominant ideology. Data were collected through observation and documentation of the film’s dialogues, then analyzed using the Gramscian model. The results show that this film is a critique of ideological domination through popular media, illustrating power relations between the dominant class and the subaltern. Alif Lam Mim represents forms of ideological hegemony that are relevant to the contemporary socio-political realities in Indonesia.